Poly(ethylene terephthalate) based blends, composites and nanocomposites - P. M., Visakh; Liang, Mong (Plastic Design Library, 2015)
Poly(Ethylene Terephthalate) (PET) is an industrially important material which is not treated specifically in any other book. Poly(Ethylene Terephthalate) Based Blends, Composites and Nanocomposites fills this gap and systematically guides the reader through all aspects of PET and its blends, composites and nanocomposites. It covers theoretical fundamentals, nanocomposites preparation, modification techniques, structure-property relationships, characterisation of the different blends and composites, and material choice for specific applications. Consisting of contributions from experts in the field this book is a useful reference for the researchers and engineers working on the development and characterization of PET materials as well as on implementing them in real-world products. It can also be used as a standard reference for deeper insight in the mechanical, thermal, thermo-mechanical and visco-elastic aspects in product design decisions.--Provided by publisher.